Integrative proteomics and metabolomics analysis of the mechanism of pancreatic β-cell dysfunction in aged mice - Pan, Fenghui; Wang, Long; He, Xuan; Rong, Can; Hu, Yun (Frontiers in Endocrinology, 2026)
ObjectivesThe prevalence of type 2 diabetes mellitus has increased worldwide and is higher among older individuals. Exploring the mechanisms underlying pancreatic β-cell dysfunction may help elucidate the pathogenesis of age-related diabetes.MethodsIslet function-related parameters were measured in four young and four aged mice. Endogenous proteins and metabolites in the pancreas were detected using liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based proteomics and metabolomics, and integrated data analysis was performed.ResultsCompared with young mice, aged mice presented higher fasting blood glucose levels and insulin resistance index (according to the homeostatic model assessment for insulin resistance, HOMA-IR), whereas that from the homeostasis model assessment of β-cell function (HOMA-β) significantly decreased. A total of 3,795 proteins were quantified, 57 of which were upregulated and 50 were downregulated in aged mice. Moreover, 46 metabolites were significantly upregulated and 19 were downregulated in aged mice. Integrated proteomic and metabolomic analyses revealed six significant pathways implicated in these changes, including arginine biosynthesis and the pentose phosphate pathway. By integrating comprehensive multi-omics data, the arginine biosynthesis-related metabolites aspartate and glutamine were found to be associated with the aging phenotype and islet function.ConclusionThese findings suggest that concurrent endogenous protein and metabolite disturbances occur in the pancreas of aged mice, and metabolite aspartate and glutamine may serve as potential biomarkers and therapeutic targets for aging-related pancreatic dysfunction.